A unified mean stress correction model for fatigue thresholds prediction of metals. (January 2020) - Liu, Yong; Paggi, Marco; Gong, Baoming; Deng, Caiyan
Highlights: A new mean stress correction model for fatigue limit and fatigue crack propagation threshold is proposed. The proposed model is verified with various commonly used metallic materials. The proposed model shows its advantage of accuracy and simplicity over the existing models. Abstract: Two fatigue characteristic thresholds, i.e. fatigue limit Δ σ e and fatigue crack propagation threshold Δ K th, have significant mean stress sensitivity. In the work, a new mean stress correction model for the two fatigue thresholds is proposed based on the cyclic strain energy density concept. Extensive experimental data in the literature is unified evenly by the proposed normalized fatigue threshold- R curves. Besides, a comparison of the proposed model with the existing models is carried out, which demonstrates that the present work can achieve more accurate predictions with the advantage of being of easy use and of being independent on any material constant.